Nanofins Science and Applications - Singh, Navdeep; Banerjee, Debjyoti; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Nanofins Science and Technology describes the heat transfer effectiveness of polymer coolants and their fundamental interactions with carbon nanotube coatings that act as nanofins. Heat transfer at micro/nano-scales has attracted significant attention in contemporary literature. This has been primarily driven by industrial requirements where significant decrease in the size of electronic devices/chips with concomitant enhancement in the heat flux have caused challenging needs for cooling of these platforms. With quantum effects kicking in, traditional cooling techniques need to be replaced with more effective technologies. A promising technique is to enhance heat transfer by surface texturing using nanoparticle coatings or engineered nanostructures. These nanostructures are termed as nanofins because they augment heat transfer by a combination of surface area enhancement as well as liquid-solid interactions at the molecular scale.
Introduction: Terminologies, Definitions and Conundrums -- Nanofins: Science -- Nanofins: Applications -- Nanofins: Implications.
Keywords: Engineering; Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Nanotechnology and Microengineering; Energy Efficiency (incl. Buildings).; Energy Systems; Energy Harvesting